Agricultural Output and Economic Growth Nexus: A VECM Approach on Bangladesh - Zobayer Ahmed; Mohammad Mizanur Rahman; Masud Pervez; Muhammad Salah Uddin (Journal of Agricultural Sciences)
Agriculture is the engine of an economy. In Bangladesh, 50% of the entire laborer force is employed in farming, and around 87% of rural families depend on agriculture for any part of their wages. Considering the importance of the agriculture sector in Bangladesh, the study examines the nexus between agricultural output and economic growth. In the finding of this causality, the VECM test has been applied and found the long-run relationship between variables where the rate of restoring the disequilibrium into equilibrium is 66.4%. The research applies the impulse response function and variance decomposition where in both cases, the result implies that the agricultural output is much more significant on economic growth than industrial output, meaning that to be a sustainable economy, the agriculture sector cannot be ignored. The study also provides insights to the policymakers that the agriculture sector should be given much more priority in terms of budget, and the academician should do more research to develop sustainable agro-based products.